Penggunaan Model Examples Non Examples untuk Meningkatkan Hasil Belajar pada Mata Pelajaran IPS Siswa SD - Karno Karno (Academy of Education Journal, 2018)
This research was based on the low learning outcomes of Social Studies students in grade IV SD Negeri 2 Adisaran odd semester 2014/2015 academic year. The research was carried out in stages, namely through cycle I and cycle II using the examples non examples model. From this research, it can be seen the results of social studies learning about the components of the map and how to read the maps obtained in pre-cycle learning, with the lowest value of 40, the highest value of 90, the average value of the class 59.52 with mastery learning 19.05%. Learning outcomes in the first cycle obtained the lowest value of 50, the highest value of 100 and an average grade of 76.66 with a mastery of learning 66.66%. The learning outcomes in the second cycle are the lowest value of 70, the highest value of 100, the average grade of 89.52 with 100% completeness of learning. The conclusion by using the examples non examples model can improve social studies learning outcomes in class IV students especially about the map components and how to read maps. Researchers hope that if there are teachers who use this learning model in order to minimize existing weaknesses.